Knockdown of Y-box binding protein 1 induces autophagy in early porcine embryos - Jiang, Wen-Jie; Lee, Song-Hee; Heo, Geun; Chung, Hak Jae; Cho, Eun Seok; Sa, Soo Jin; Hochi, Shinichi; Cui, Xiang-Shun (Frontiers in Cell and Developmental Biology, 2023)
Y-box binding protein 1 (YBX1) plays important roles in RNA stabilization, translation, transcriptional regulation, and mitophagy. However, its effects on porcine preimplantation embryos remain unclear. In this study, we knocked down YBX1 in the one-cell (1C) stage embryo via small interfering RNA microinjection to determine its function in porcine embryo development. The mRNA level of YBX1 was found to be highly expressed at the four-cell (4C) stage in porcine embryos compared with one-cell (1C) and two-cell (2C) stages. The number of blastocysts was reduced following YBX1 knockdown. Notably, YBX1 knockdown decreased the phosphatase and tensin homolog-induced kinase 1 (PINK1) and parkin RBR E3 ubiquitin protein ligase (PRKN) mRNA levels. YBX1 knockdown also decreased PINK1, active mitochondria, and sirtuin 1 levels, indicating reduced mitophagy and mitochondrial biogenesis. Furthermore, YBX1 knockdown increased the levels of glucose-regulated protein 78 (GRP78) and calnexin, leading to endoplasmic reticulum (ER) stress. Additionally, YBX1 knockdown increased autophagy and apoptosis. In conclusion, knockdown of YBX1 decreases mitochondrial function, while increasing ER stress and autophagy during embryonic development.